2015
DOI: 10.1183/13993003.01669-2015
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for idiopathic pulmonary fibrosis: lessons from pooled data analyses

Abstract: @ERSpublicationsThe pooled analysis of three large phase 3 trials sheds further light on the role of antifibrotic therapy in IPF http://ow.ly/UNTWQ In 2014, two landmark clinical trials (ASCEND and INPULSIS) were published demonstrating, for the first time, a treatment benefit for patients with idiopathic pulmonary fibrosis (IPF). Both pirfenidone and nintedanib were shown to have a clear therapeutic benefit in slowing the relentless disease progression evident in IPF patients. The results of these studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Interestingly, when we examined the IPF phenotype after pirfenidone or nintedanib treatment, we found a reduction in the levels of FN and collagen but SMA levels remained high ( Figure 9G ). This result is consistent with the observation that while both drugs are beneficial to a percentage of patients with IPF, either drug only slows the progression of disease ( Myllarniemi and Kaarteenaho, 2015 ; Troy and Corte, 2016 ). To examine the morphological consequences of nintedanib and pirfenidone treatment on IPF cells, we stained for stress fibers.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, when we examined the IPF phenotype after pirfenidone or nintedanib treatment, we found a reduction in the levels of FN and collagen but SMA levels remained high ( Figure 9G ). This result is consistent with the observation that while both drugs are beneficial to a percentage of patients with IPF, either drug only slows the progression of disease ( Myllarniemi and Kaarteenaho, 2015 ; Troy and Corte, 2016 ). To examine the morphological consequences of nintedanib and pirfenidone treatment on IPF cells, we stained for stress fibers.…”
Section: Resultssupporting
confidence: 92%
“…Currently, there are no effective therapies for IPF, which is typically fatal within 2–3 yr of diagnosis. However, in 2014 two drugs, pirfenidone and nintedanib, were approved for IPF patients after being found to be beneficial although not curative ( Myllarniemi and Kaarteenaho, 2015 ; Troy and Corte, 2016 ). Nintedanib is a tyrosine kinase inhibitor that acts on several receptor tyrosine kinases (PDGFR, FGFR, and VEGFR) ( Hilberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments we have found that Rnd3 levels are depressed when normal and breast cancer epithelial cells are cultured on more rigid substrates (E Monaghan-Benson 2018, unpublished results), suggesting that this pathway may be important in elevating RhoA activity in tumours. In previous work we found that drugs such as nintedanib and pirfenidone, which have been used to treat IPF [62,63], elevate Rnd3 expression and thereby decrease RhoA activity [57]. This raises the possibility that these drugs may also have therapeutic potential for solid tumours.…”
Section: Mechanical Force and Rho Gtpase-activating Proteinsmentioning
confidence: 99%
“…Clinical trials have demonstrated that nintedanib and pirfenidone inhibit the annual rate of decline of FVC in patients with IPF 5–8 . The efficacy of AFT on lung function was consistent in patients with IPF with preserved lung function as well as in those with impairments in lung function 18,20–22 . Furthermore, the effects were sustained for a long time, 23 suggesting that prompt treatment is beneficial for patients with IPF.…”
Section: Discussionmentioning
confidence: 92%
“…Besides its efficacy on the annual rate of decline in FVC, emerging evidence has confirmed that antifibrotic therapy (AFT) reduces the risks of acute exacerbation (AE), 16 respiratory-related hospitalization 17 and disease progression. 18 However, AFT was administered to only 60% of patients with IPF and certain time lags existed between diagnosis and AFT initiation. Furthermore, sufficient evaluation has not been done to determine disease course and prognostic determinants in patients with IPF based on the characteristics measured at AFT initiation.…”
Section: Introductionmentioning
confidence: 99%